Desflurane Allows for a Faster Emergence When Compared to Sevoflurane without Affecting the Baseline Cognitive Recovery Time - Werner, Joseph G.; Castellon-Larios, Karina; Thongrong, Cattleya; Knudsen, Bodo E.; Lowery, Deborah S.; Antor, Maria A.; Bergese, Sergio Daniel (Frontiers in Medicine, 2015)
Aims We compared the effect of desflurane and sevoflurane on anesthesia recovery time in patients undergoing urological cystoscopic surgery. The Short Orientation-Memory-Concentration Test (SOMCT) measured and compared cognitive impairment between groups and coughing was assessed throughout the anesthetic. Methods and materials This investigation included 75 ambulatory patients. Patients were randomized to receive either desflurane or sevoflurane. Inhalational anesthetics were discontinued after removal of the cystoscope and once repositioning of the patient was final. Coughing assessment and awakening time from anesthesia were assessed by a blinded observer. Statistical analysis used Statistical analysis was performed by using t-test for parametric variables and Mann–Whitney U test for non-parametric variables. Results The primary endpoint, mean time to eye-opening, was 5.0 ± 2.5 min for desflurane and 7.9 ± 4.1 min for sevoflurane (p < 0.001). There were no significant differences in time to SOMCT recovery (p = 0.109), overall time spent in the post-anesthesia care unit (PACU) (p = 0.924) or time to discharge (p = 0.363). Median time until readiness for discharge was 9 min in the desflurane group, while the sevoflurane group had a median time of 20 min (p = 0.020). The overall incidence of coughing during the perioperative period was significantly higher in the desflurane (p = 0.030). Conclusion We re-confirmed that patients receiving desflurane had a faster emergence and met the criteria to be discharged from the PACU earlier. No difference was found in time to return to baseline cognition between desflurane and sevoflurane.